Zarys osiągnięć w dziedzinie modelowania gospodarstw rolnych - Sobków, Czesław (Wydział Prawa i Administracji UAM, 1974)
The method of modelling in the economic agricultural research plays the same role as an experience in the biological sciences. This method can be useful for the introduction of progress and for the choice of production an the individual farms.
Some Research Results in the Problem of Farm Modeling